2012
DOI: 10.1111/j.1747-4949.2012.00815.x
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Direct Medical Costs of Stroke in Korea: A Multi-Centre Incidence-Based Study from Hospital Perspectives

Abstract: Direct medical costs for stroke in Korea were determined, which seem to be lower than those of other developed countries. Female gender, young age, and first stroke were factors related to higher stroke cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
12
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 18 publications
5
12
4
Order By: Relevance
“…The variation in costs of different subtypes of stroke might be attributable to disease severity and cost composition. Regarding SAH that was reported for the first time in China, the hospitalization cost was the highest, the same as previous studies reported in other countries [9, 10]. In this study, the biggest proportion of total hospitalization costs for SAH patients was spent on non-medication treatment, probably due to a more serious condition such as ruptured intracranial aneurysm, which usually requires neurosurgery and intensive care monitoring [26, 27].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The variation in costs of different subtypes of stroke might be attributable to disease severity and cost composition. Regarding SAH that was reported for the first time in China, the hospitalization cost was the highest, the same as previous studies reported in other countries [9, 10]. In this study, the biggest proportion of total hospitalization costs for SAH patients was spent on non-medication treatment, probably due to a more serious condition such as ruptured intracranial aneurysm, which usually requires neurosurgery and intensive care monitoring [26, 27].…”
Section: Discussionsupporting
confidence: 83%
“…When comparing our results with findings in other countries, a large variation in costs are observed. The average hospitalization cost (CNY 20,203.1 = US $3212.1) reported in this study was much lower than that in other countries, compared to US$20,396 (2008 price) in the United States [6], €5328 (US$6845, 2012 price) in Netherlands [16], €9004 (US$8104, 2001 price) in Sweden [12], S$12,473.7 (US$10,190, 2012 price) in Singapore [10], US$8732 (2007 price) in South Korea [9] and US$8662 (2002 price) in Japan [8]. Nevertheless, the international comparison of the average healthcare cost for stroke was limited by different estimation approaches (prevalence-based or incidence-based), different types of costs (inpatient or outpatient services), different number of stroke subtypes (one or five subtypes), and different phases of stroke (acute or prevalent stroke, first-ever or recurrent stroke) included in those studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher patient healthcare cost in the CE subtype of ischemic stroke might be explained by the fact that patients in this subpopulation had more serious disease that required cardiac surgery. Rha et al reported that the difference in cost was not significant after one year, because of most medical costs were expended within the first year following stroke, including for the inpatient care, acute nursing, surgery, and rehabilitation, and after a year, the medical charges were similar [14]. The lower total cost at one year in the UND subtype was due to lower outpatient costs, but with higher inpatient cost due to the need to undertake a range of investigations to determine the etiology of the ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…These treatments are costly. Although hemorrhagic strokes are more costly in the acute stage, long-term care is significantly more expensive for secondary prevention of ischemic stroke 4. Furthermore, stroke survivors, especially those who develop recurrent strokes, are often disabled, depressed, and cognitively impaired.…”
mentioning
confidence: 99%